Hypomyelinating Leukodystrophy due to HSPD1 Mutations: A New Patient - Kusk, Maria Schioldan; Damgaard, Bodil; Risom, Lotte; Hansen, Bente; Ostergaard, Elsebet (Neuropediatrics, 2016)
The hypomyelinating leukodystrophies (HMLs) encompass the X-linked Pelizaeus–Merzbacher disease (PMD) caused by PLP1 mutations and known as the classical form of HML as well as Pelizaeus–Merzbacher-like disease (PMLD) (Online Mendelian Inheritance in Man [OMIM] 608804 and OMIM 260600) due to GJC2 mutations. In addition, mutations in at least 10 other genes are known to cause HMLs. In 2008, an Israeli family with clinical and neuroimaging findings similar to those found in PMD was reported. The patients were found to have a homozygous missense mutation in HSPD1, encoding the mitochondrial heat-shock protein 60 (Hsp60), and the disorder was defined as the autosomal recessive mitochondrial Hsp60 chaperonopathy (MitCHAP-60) disease. We here report the first case of this severe neurodegenerative disease since it was first described. Given the fact that the families carried the same mutation our patient probably belongs to the same extended family as the Israeli family. In conclusion, the MitCHAP-60 disease should be considered as a rare differential diagnosis in HML.
Keywords: Pelizaeus–Merzbacher disease; brain hypomyelination; exome sequencing; mitochondrial Hsp60 chaperonopathy